Environmental resistance materials in PAUD Merdeka curriculum project modules - Setyaningrum, Mila; Wulansari, Betty Yulia; Rusdiani, Nurtina Irsad (Pusat Studi Gender dan Anak, 2024)
Early childhood need to receive stimulation to be sensitive to the environment. If children have developed a sense of caring for the environment, they will understand their responsibility in maintaining the environment around them. This research describes the material used to preserve the natural environment in the Merdeka curriculum. The type of research used is descriptive qualitative. This research approach uses a literature study method or literature study that uses journals or scientific articles, books, and references related to environmental conservation materials. Based on the research results, it can be concluded that Environmental resistance materials in the Early Childhood Education of Merdeka curriculum, which can be applied are 1) Cleanliness of the Natural Environment Applied, for example, children throw rubbish in the right place 2) Recycle rubbish; Applied example; children make crafts from used bottles, 3) Reforestation; Applied example; children plant trees in the school environment, 4) Mitigation Applied examples children are given examples of how to save themselves during an earthquake. 5) Go Green: Applied examples; children bring drinking bottles that can be used repeatedly (not plastic).